Caracterização molecular, anatômica e fisiológica de genótipos de Manihot esculenta (Crantz) com subsessilidade foliar - Cabral, Serli de Oliveira (2023)
The cassava (Manihot esculenta), commonly known as yuca or manioc, is extensively cultivated in tropical and subtropical regions and is one of the primary food crops. There is a growing interest in improving cassava for industrial applications, such as the production of biofuels and ethanol, making Active Germplasm Banks (AGBs) essential for conserving and selecting genotypes with desirable agronomic and industrial characteristics. One aspect that has been relatively unexplored is the foliar subsessility phenotype, which is present in certain cassava genotypes. The hypothesis is that these genotypes may offer advantages in field conditions due to their reduced petiole size, leading to a more efficient distribution of assimilates and, consequently, improved productivity. This characteristic can be leveraged in the development of more productive and resistant varieties using gene editing techniques. The objective of this research was to characterize, describe, and compare two cassava genotypes with the foliar subsessility phenotype at the molecular, anatomical, and physiological levels. Molecular, anatomical, and physiological analyses provided valuable information, enhancing the understanding of the implications of this phenotype. The results from field and physiological observations indicate that foliar subsessility in genotypes M1 and M2 influences the plant's canopy architecture, resulting ina "bouquet" configuration with overlapping leaves. This configuration demonstrated higher light capture efficiency, with higher levels of chlorophyll a and b, suggesting greater photosynthetic potential and possibly a higher plant density per hectare. In addition, a unique growth gradient was identified in these subsessile genotypes that require more detailed investigations into the hormonal factors involved in this process. Molecular analyses revealed that, despite similarities in phenotypic patterns, no specific background genetic pattern was identified associated with the foliar subsessility phenotype, indicating that this variation may occur spontaneously in any genotype or variety. Furthermore, notable differences were observed in the anatomy of stabilized short petioles, including the presence of a shell-like structure surrounded by filling/fundamental parenchyma cells and the absence of cambium. These results suggest that the variation found in genotypes with foliar subsessility may be associated with differential responses to edaphoclimatic factors, but further complementary assays are needed for a more comprehensive explanation. Understanding the genetic factors that control this phenotype is crucial for the genetic improvement of the cassava crop. Additional research at the transcriptome and proteome levels of these genotypes can contribute to mapping the genetic factors responsible for the subsessility phenotype, paving the way for expanding the potential of this crop through Innovative Techniques in Precision Breeding (ITPBs).